Blockchain-enabled weather index crop insurance for smallholder farmers - Muvhu, Tatenda (School of Economics, 2025)
Weather index crop insurance is an innovative approach to protect farmers against financial losses incurred due to adverse weather events that reduce crop yield. This type of insurance has the potential to be more affordable to underprivileged communities in emerging economies as it incurs lower transaction costs compared to conventional insurance, and it reduces both adverse selection and moral hazard in insurance provision. This thesis designs and implements a weather index crop insurance platform on the Algorand blockchain to enable low-cost, secure, transparent, efficient and easily verifiable transactions between weather data providers, insurers and farmers. To guide the implementation, an examination of the present state of weather index crop insurance in South Africa, its benefits and limitations, and the possibility of using blockchain technology to tackle some of the challenges faced by smallholder farmers when using conventional crop insurance methods is done. These challenges include long claim cycles, costly claim disputes and paper-heavy policies. The prototype weather index crop insurance platform improves the efficiency of the insurance process for weather data management, insurance policy management and insurance payouts processing. The platform stores transactions on the blockchain for transparency and verifiability and streamlines the insurance payout process with the use of auto-triggered payouts when weather data-dependent strike conditions attached to an insurance policy are met. Additionally, it digitizes policy management, eliminating the need for paper. Tests on the platform show that a farmer's request to join an insurance policy is finalized in an average of 9.13 seconds, from clicking “Join” to confirming the transaction and logging details on the blockchain. This process incurs a fixed transaction fee of 0.001 ALGO (approximately ZAR 0.002 as at 06/08/2023). Compared to traditional insurance applications, which take days to confirm, this is significantly faster and cheaper. Payouts on the platform are processed with an average processing time of 16 seconds from the detection of a strike event, in sharp contrast with conventional insurance where payout processing can take days. Further, in contrast to traditional insurance schemes, the weather index crop insurance platform requires fewer communication rounds between insurance actors. This benefits farmers with a simplified insurance policy enrollment process, reduced administrative burden, and faster payout processing. Load tests show that deploying the platform behind a load balancer, which distributes workload across multiple resources, enhances response time and overall performance, enabling it to handle more concurrent requests.